2013
DOI: 10.1021/nn401487m
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Heterogeneously Charged Particles under Confinement

Abstract: Self-assembly—the spontaneous organization of microscopic units into well-defined mesoscopic structures—is a fundamental mechanism for a broad variety of nanotechnology applications in material science. The central role played by the anisotropy resulting from asymmetric shapes of the units and/or well-defined bonding sites on the particle surface has been widely investigated, highlighting the importance of properly designing the constituent entities in order to control the resulting mesoscopic structures. Anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 35 publications
5
76
0
Order By: Relevance
“…IPCs have been observed to form similar structures as the ones encountered here both in simulations 71,72 as well as in experiments. Appendix A: Two particle ground state configurations at particle contact…”
Section: 69supporting
confidence: 80%
“…IPCs have been observed to form similar structures as the ones encountered here both in simulations 71,72 as well as in experiments. Appendix A: Two particle ground state configurations at particle contact…”
Section: 69supporting
confidence: 80%
“…In particular, numerical investigations on IPC systems with two identical polar patches have shown that an emerging feature of such systems is the formation of planar aggregates either as monolayers closed to a charged substrate 94,95 or as bulk equilibrium phases. 109,110 Close to a homogeneously charged substrate, IPCs with two identical patches form assemblies with well-defined translational and orientational order depending on the charge ratio of the different entities involved, the patch size and the interaction range (see Fig.…”
Section: Charged Patchy Colloidsmentioning
confidence: 99%
“…2). 94,95 The features of these assemblies depend on the system parameters and were proven to reversibly respond to changing conditions such as the pH of the solution and the charge of the substrate. 95 It is worth noting that the same morphological features observed in simulations have been found in experimental samples of IPCs sedimented on a glass substrate; 41 however, while all clusters in the same numerical sample have the same spatial and orientational order, experimental IPCs form different particle arrangements within the same sample, probably due to the patch polydispersity.…”
Section: Charged Patchy Colloidsmentioning
confidence: 99%
“…This type of functionalization allows a very detailed control on of colloidal valence, strength, and selectivity of the colloidal bonds. During self-assembly, the chemical nature (or strength) of the patch-patch interaction leads to large energy barriers impeding the formation of equilibrium structures, promoting kinetically trapped structures, such as gels, glasses or polycrystals [1,[21][22][23][24][25]. One route to control the assembly of non-equilibrium structures is the use of flat or patterned substrates [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%